Technology-enhanced learning on campus: insights from EUNIS e-Learning Task Force - Ferrell, Gill (2014)
In 2010 the EUNIS e-Learning Task Force (ELTF) members collaborated on a review of tools and technologies in use across our member institutions. One of the key features of that paper was the use of technology to give off-campus learners, such as distance learners, those undertaking field studies and learners in the workplace a richly supported learning experience. Building on the success of that collaboration, the ELTF members have turned their attention this year to the use of technology on campus. Whilst technology and distance learning go hand in hand, universities are often slower to take advantage of the possibilities offered by technology to enrich the learning that takes place in our lecture theatres and classrooms. The reasons for this are often cultural as much as financial or technical. Drawing on experience from across the EUNIS member nations we take a look at the types of tools, learning resources and learning activities that are being used to enhance the traditional curriculum, promote deeper learning and bridge the learning that takes place inside and outside the classroom. We look at a range of innovative projects and the benefits they have delivered, ways of overcoming the barriers to technology-enhanced learning on campus and we speculate about the role and function of the campus of the future …